Risk factors for hip fracture in elderly persons - P. Olivi; S. Giannini; S. Sella; R. Lovato; M.C. Spenevello; S. Pancheri; C. Benini; C. Zambarda; O. Viapiana; V. Braga; A. Mattarei; M. Rossini; et al. (Reumatismo, 2011)
Objective: The aim of this observational study, promoted by the Health Authorities of the Regione Veneto (Italy), is to assess the prevalence of the most relevant environmental and individual risk factors in subjects with a recent hip fracture. Methods: Patients aged more than 60 years of both genders with a recent hip fracture not associated with malignancies, were administered questionnaires on dietary habits, sun exposure, and disability score. A complete family, pharmacological and pathology history was collected together with information on previous falls, details of the fracture index, and anthropometric data. In all subjects, blood was taken for the measurement of serum 25 hydroxy-vitamin D (25OHD). Results: The study included 704 patients (573 women and 131 men). Mean age was 81±8 years (range 60-102). Severe pre-fracture disability was a common feature (58%) associated with multiple co-morbidities (84%), more frequently cardio- vascular and neurological diseases, and specific medications. In a large proportion (86%) of the patients, environmental or individual risk factors for falling were found. Vitamin D insufficiency (serum 25OHD levels <75 nmol/l) was quite common (70%), particularly in the regional Health Districts were strategies for preventing vitamin D deficiency were not implemented (91%). Only a small proportion (17%) of the study population had been evaluated and treated for osteoporosis. Conclusions: In senile patients with a recent hip fracture, pre-existing disability, multiple co-morbidities, high risk of falling and inadequate intake of calcium and vitamin D is relatively common. Community and case-finding interventions aimed at selecting subjects at high risk of osteoporosis, preventing vitamin D and dietary calcium deficiency, and increasing awareness on the environmental risks of falling are highly warranted.